(3CLhHI GdEeGe GdCYXe CHj MfjaIs - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdYGbHI ddeJbjf hdGYOhGf EdG Ydi GdXGdejf s
(3BNQgG (B:s
(3ai CQHYI CQWGd ajUM GdMSGH hGddg CYde hGdMeO ddg QH GdYGdejf hMSHfG Gddg hfYe Gdhcjd s
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCRgQjI (B((3abg Mfai (B946) s
Keywords: (3Gdabg GdMfajs